Islamic Aqidah Education for Families in View of the Perspective of Alqur'an Surah Luqman Verses - Sofan, Muhamad; Wage, Wage; Darojat, Darojat (Journal La Sociale, 2025)
The Qur'anic perspective on the family emphasizes the importance of close and supportive relationships between family members. The Qur'an provides guidelines regarding clear roles and responsibilities for each family member, such as the father as the leader and organizer of the economy, and the mother who educates the children. In the context of husband-wife relationships, the Qur'an emphasizes the importance of justice and equality. Families are also taught to have unity of purpose in worshipping Allah SWT and creating pious generations. In addition, forgiveness and forgiveness among family members are important principles to maintain harmony. The Qur'an portrays the family as an important institution in shaping the character, morals and spirituality of Muslims.